Anti-microbial, anti-oxidant, and anti-breast cancer properties unraveled in yeast carotenoids produced via cost-effective fermentation technique utilizing waste hydrolysate - Sinha, Sweta; Das, Souvik; Saha, Biswajit; Paul, Debarati; Basu, Biswarup (Frontiers in Microbiology, 2023)
Vegetable “mandi” waste was used to prepare waste hydrolysate, a culture medium, in which oleaginous red yeast Rhodosporidium sp. was grown. Carotenoid pigments were extracted using solvent extraction method and analysed by UV spectroscopy, TLC and HPLC. Antimicrobial, antioxidant and anticancer activities of the extract were evaluated, followed by in silico docking and ADME/T studies. Carotenoids extract was found to be composed of three main pigments- β-carotene, torulene, and torularhodin. Extract exhibited significant antioxidant, antimicrobial and anti-breast cancer activities in vitro while being biocompatible. In silico evaluation predicted binding with breast cancer specific molecular targets, good drug likeliness properties, and less toxicity. This is the first report on anti-breast cancer activities, particularly in triple negative breast cancer cells, by red yeast carotenoids produced via a sustainable environment friendly bioprocess utilising waste hydrolysate.